Determinação de íons cobre(II) em aguardente de cana-de-açúcar utilizando a combinação spot test - espectroscopia de reflectância difusa - Souza, João Carlos de [UNESP] (2015)
The presence of high concentrations of copper(II) ions in sugarcane spirits become harmful to human health and is also one of the causes that have prevented Brazil from achieving higher levels of exports of the product. The maximum limit of copper in spirit allowed by MAPA (Ministry of Agriculture, Livestock and Supply) is 5.00 mg.L-1, and in European Union countries and the United States these limits are more stringent, not allowing more than 1.00 e 2.00 mg.L-1 respectively. In light of the above, this work proposes a new analytical method that is simpler, fast, safe, sensitive, economical, portable, with low reagent consumption, generating minimal waste and environmentally more friendly for the determination of copper(II) ions in Brazilian sugarcane spirits. To process the reaction, the methodology used involved chromogenic agent 1-(2-pyridylazo)-2-naphthol (PAN) and detection by diffuse reflectance spectroscopy combined with spot test. The reaction of complex formation bis[1-(2-pyridylazo)-2-naphthalate]copper(II) (Cu(PAN)2) was carried out on a filter paper through the addition of 30 μL solution of the chromogenic reagent with subsequent drying of the paper, and 30 μL of analyte solution was added thereafter. The maximum product formation occurred at 559 nm with PAN chromogenic agent concentration of 0.12% m/v in ethanol, alcohol concentration of 40.0% v/v at pH 5.0 and 5 minute reaction time. Cadmium(II) ions, cobalt(II), lead(II), iron(III), manganese(II), nickel(II) and zinc(II) were found to interfere in the reaction. By virtue of that, malonic acid and pentasodium tripolyphosphate (sodium triphosphate) were used as masking agents at a concentration of 0.25% m/v, reducing the effects of interference at about 2.0% and leaving it within tolerable limits. In order to optimize the determination of copper(II) ions, an analytical curve was constructed and its equation is described by...